Kajian Literatur Antara Sistem Endokrin dan Imun dalam Kerja Sama Hormon dan Pertahanan Tubuh untuk Pembelajaran Biologi - Resita Dewi; Avrellia Dwi Riantini; Suci Mairani (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
The endocrine system and the immune system are two main physiological systems that play an important role in maintaining body balance (homeostasis) and defending the body from various external threats such as infections, toxins, and stress. Both do not work independently, but rather establish complex interactions through various biochemical pathways, including hormones and cytokines. Recent research has shown that disorders in one system can affect the function of the other system. This article aims to review the relationship between the endocrine system and the immune system, with a focus on the cooperation of hormones in supporting the body's defense. This study uses a literature study method based on the latest scientific journals in the last five years. The results show a two-way interaction between endocrine hormones such as glucocorticoids, thyroid hormones, and sex hormones on immune function, both stimulatively and suppressively. Understanding this relationship is important for the development of more effective and integrated immunology and endocrinology therapies.